2019
DOI: 10.35787/jimdc.v8i3.419
|View full text |Cite
|
Sign up to set email alerts
|

Use of Zinc and Oral Rehydration Solution in Home Management of Diarrhea: Knowledge of Mothers of attending a Tertiary Care Hospital

Abstract: Background: Diarrhea is the second leading cause of mortality in children below 5 years of age in Pakistan. Use of Zinc and ORS has been proven in clinical trials to be beneficial in reducing morbidity and mortality. Poor knowledge regarding home management of diarrhea leads to mortality due to severe dehydration. The objective of this study was to assess the level of knowledge of mothers of under five-year-old children regarding, diarrheal home management in Cantonment General Hospital, Rawalpindi. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similarly, the cultural practice of food abstinence during diarrhoeal illness and lack of maternal knowledge about diarrhoea case management also contributes to the low adherence [ 34 ]. Different studies conducted in Pakistan reflected that most mothers are well aware of zinc and ORS use for managing paediatric diarrhoea [ 18 , 35 , 36 ]. However, a study conducted in the urban slums of Karachi reported inappropriate diarrhoea case management practices despite having adequate knowledge regarding diarrhoea case management [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cultural practice of food abstinence during diarrhoeal illness and lack of maternal knowledge about diarrhoea case management also contributes to the low adherence [ 34 ]. Different studies conducted in Pakistan reflected that most mothers are well aware of zinc and ORS use for managing paediatric diarrhoea [ 18 , 35 , 36 ]. However, a study conducted in the urban slums of Karachi reported inappropriate diarrhoea case management practices despite having adequate knowledge regarding diarrhoea case management [ 18 ].…”
Section: Discussionmentioning
confidence: 99%